Strain ratio effect on microstructural evolution during low cycle fatigue exploitation of nickel base superalloy IN 740H. (15th December 2021) - Kumar, C.; Jena, P.S.M.; Singh, R.K.; Harmain, G.A.; Sahu, J.K.
Abstract: Strain ratio ( R ε ) is varied during isothermal strain-controlled fatigue tests of nickel-base superalloy IN740H at 760 °C; R ε = −1, 0, 0.5. Unlike most alloys, highest fatigue life is observed under R ε = 0 test condition compare to R ε = 0.5 and −1. From extensive electron microscopy, i.e. energy-filtered TEM (EF-TEM), WDS and EDS studies, it is confirmed that the creep effect due to tensile mean stress under R ε = 0 condition was offset due to segregation of Nb at dislocation and formation of Nb(CN) at grain boundaries, which proved to be fatigue strengthening. Debonding of Nb(CN) and γ matrix provided preferential fatigue crack initiation sites and resulted in lowering the fatigue life for R ε = 0.5 test condition. Highlights: Isothermal low cycle fatigue (LCF) test was conducted in IN 740H alloy at 760 °C by employing different strain ratio ( R ε ) and different strain amplitude. Unlike most alloys, the highest fatigue life is observed under R ε = 0 test conditions compare to R ε = 0.5 and −1. From extensive electron microscopy analysis it was found that the LCF life is improved by retardation of fatigue crack growth caused by Nb(CN) precipitated at grain boundaries in R ε = 0 test condition.